2022
DOI: 10.3389/fmolb.2022.916689
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Prognosis in Patients With Endometrial Carcinoma and Immune Microenvironment Estimation Based on Ferroptosis-Related Genes

Abstract: Background: Ferroptosis, a form of non-apoptotic cell death, has aroused worldwide interest in cancer researchers. However, the current study about the correlation between ferroptosis-related genes (FRGs) and endometrial cancer (EC) remains limited.Methods: First, the transcriptome profiling and clinical data of EC patients were downloaded from The Cancer Genome Atlas (TCGA) and Clinical Proteomic Tumor Analysis Consortium (CPTAC) program as the training group and testing group, respectively. FRGs were acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…Hsiao et al reported that TRL4 is a target for suppression of proliferation and chemoresistance in HepG2 HB cells 18 . Consistence with our results, some researches revealed that TRL4 is a ferroptosis-signi cant adverse-selected gene promoting tumor poor prognosis in multiple models, like breast cancer 19 , gastric cancer 20 , endometrial carcinoma 21 , lung adenocarcinoma 22 . These suggested that TRL4 may involve in ferroptosis-related HB tumor progression.…”
Section: Discussionsupporting
confidence: 89%
“…Hsiao et al reported that TRL4 is a target for suppression of proliferation and chemoresistance in HepG2 HB cells 18 . Consistence with our results, some researches revealed that TRL4 is a ferroptosis-signi cant adverse-selected gene promoting tumor poor prognosis in multiple models, like breast cancer 19 , gastric cancer 20 , endometrial carcinoma 21 , lung adenocarcinoma 22 . These suggested that TRL4 may involve in ferroptosis-related HB tumor progression.…”
Section: Discussionsupporting
confidence: 89%
“…Waterfall plots were constructed using the ‘maftools’ package in R to determine the frequency of point mutations in samples and examine the relationship between TMB and risk scores ( Liu S. et al, 2023 ). The effectiveness of targeted therapy was forecasted using the ‘pRRophetic’ package ( Liu et al, 2022 ). Sensitivity to different drugs was assessed using the semi-maximum inhibitory concentration index (IC50) to explore the therapeutic advantages for ovarian cancer patients ( Liu S. et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Inhibiting SLC7A11 causes GSH depletion ( Dixon et al, 2012 ). Down-regulating system xc− by targeting TP53 ( Jiang et al, 2015 ; Liu S. et al, 2022 ), NFE2L2 ( Chen et al, 2017 ), BAP1 ( Zhang et al, 2018 ), BECN1 or OTUB1( Song et al, 2018 ), can reduce GSH synthesis, enhance ROS generation, and result in ferroptosis. GPX4 belongs to GSH peroxidases and it is an antiferroptotic molecular ( Seibt et al, 2019 ).…”
Section: Molecular Mechanism Of Ferroptosismentioning
confidence: 99%